The Impact of ESG Disclosure, Hedging Policy, and Cash Holding on Firm Value - Lestari, Tri Utami; Hasanah, Sri Indah (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
This study aims to examine the effect of ESG disclosure, hedging policy, and cash holdings on firm value. The sampling method employed is purposive sampling, focusing on energy sector companies listed on the Indonesia Stock Exchange. The sample consists of 11 companies over the period from 2018 to 2023, yielding a total of 60 observations. The data utilized in this research are secondary, obtained from annual reports and sustainability reports of the companies. Data analysis is conducted using panel data regression analysis. The findings indicate that ESG disclosure does not have a significant impact on firm value. This study reveals that many companies in Indonesia have yet to implement sustainability concepts or publicly disclose ESG information. ESG disclosure remains in a developmental stage and has not been widely adopted, thus it is not a primary consideration for investors. Conversely, the hedging policy positively affects firm value, suggesting that companies that implement hedging strategies can enhance their value. Meanwhile, cash holdings do not exhibit a significant influence on firm value.